2022
DOI: 10.1149/1945-7111/ac5bae
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of Paraquat Using Gold Nanoparticle Incorporated Multiwalled Carbon Nanotubes

Abstract: The present work focuses on electrochemical estimation of the herbicide, paraquat using Au nanoparticle incorporated multi-walled carbon nanotube (AuNP-MWCNT). The catalyst was synthesised and characterised using physical characterization techniques like HRSEM, HRTEM, Raman spectroscopy, and XRD. The techniques reveal the successful incorporation of Au nanoparticles onto MWCNT and it was utilized for the electrochemical determination of paraquat (PQ). The AuNP-MWCNT modified glassy carbon electrode (AuNP-MWCNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition to that, there are other possibilities such as comproportionation reaction between PQ 2+ and PQ ). 21 Hence, it is concluded that the obtained anodic peaks are due to the mass transfer and surface adsorption process. Cyclic voltammetric response of CMK-3/GCE in the presence as well as the absence of PQ in PBS (pH = 9.2) was recorded and provided as Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to that, there are other possibilities such as comproportionation reaction between PQ 2+ and PQ ). 21 Hence, it is concluded that the obtained anodic peaks are due to the mass transfer and surface adsorption process. Cyclic voltammetric response of CMK-3/GCE in the presence as well as the absence of PQ in PBS (pH = 9.2) was recorded and provided as Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Among the developed catalysts, carbon-based materials were found to be effective in the determination of PQ. Bare as well as functionalized carbon matrices such as gold-modified multi-walled carbon nanotubes (MWCNTs), 21 silver particles over carbon paste electrode, 25 carbon paste electrode with biochar, 26 metal-organic frameworks, and para sulfonatocalix [4]arene-gold nanoparticle composite, 27 carboxylatopillar [5]arenecoated nitrogen-doped carbon dots, 28 flexible laser-induced graphene, 29 boron/nitrogen-co-doped carbon nanosheets decorated with Fe 2 O 3 nanocrystals, 30 molecularly imprinted polymer membrane on a glassy carbon electrode modified with Au nanocross-chitosan, 31 rGO-CuS hybrid, 32 and amorphous carbon@CuFeS 2 -PVP 33 have been explored for the electrochemical biosensor applications. In addition to these matrices, the role of functionalized ordered mesoporous carbon, CMK-3 has also been found effective for the electrochemical determination of various analytes like hydrazine.…”
mentioning
confidence: 99%
“…Paraquat has adverse effects on living organisms and the environment, so controlling its level in the soil is crucial. AuNPs have been used in a number of electrochemical detection methods for paraquat due to their effective electrocatalytic performance, and a nanomole-level detection line has been established [ 100 , 101 , 102 ]. For example, Aliakbar et al [ 101 ] prepared a catex polymeric-AuNPs composite modified electrode for determining paraquat based on the redox property of paraquat.…”
Section: Application Of Nanoparticle-based Sensors For Different Pest...mentioning
confidence: 99%
“…Generally, electrodes were modified by metal nanoparticles, reduced graphene oxide, multi-walled carbon nanotubes (MWCNTs), 40 quantum dots and biomass materials, dyes, etc. Owing to excellent conductivity and adsorption properties of these material, the electrochemical properties of the substrate electrodes are improved, with heightening analytical sensitivity.…”
mentioning
confidence: 99%